2010
DOI: 10.2174/187152710793361586
|View full text |Cite
|
Sign up to set email alerts
|

Heteromerization of G Protein-Coupled Receptors: Relevance to Neurological Disorders and Neurotherapeutics

Abstract: Because G protein-coupled receptors (GPCRs) are numerous, widely expressed and involved in major physiological responses, they represent a relevant therapeutic target for drug discovery, particularly regarding pharmacological treatments of neurological disorders. Among the biological phenomena regulating receptor function, GPCR heteromerization is an important emerging area of interest and investigation. There is increasing evidence showing that heteromerization contributes to the pharmacological heterogeneity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 163 publications
(236 reference statements)
0
39
0
Order By: Relevance
“…Several diseases or pathogenic conditions are associated with the function of this receptor including autism and schizophrenia (Gimpl & Fahrenholz 2001). It was recently reported that OTR and vasopressin receptors form homo-and heterodimers in vitro and in vivo (Albizu et al 2010b). Negative cooperative binding of oxytocin at the OTR was observed in in vitro systems, which points to a functional significance of dimerization (Albizu et al 2006).…”
Section: R68 Reviewmentioning
confidence: 99%
“…Several diseases or pathogenic conditions are associated with the function of this receptor including autism and schizophrenia (Gimpl & Fahrenholz 2001). It was recently reported that OTR and vasopressin receptors form homo-and heterodimers in vitro and in vivo (Albizu et al 2010b). Negative cooperative binding of oxytocin at the OTR was observed in in vitro systems, which points to a functional significance of dimerization (Albizu et al 2006).…”
Section: R68 Reviewmentioning
confidence: 99%
“…The scope of functional understanding of neuropeptide actions has been further extended by the discovery of direct receptor-receptor interactions suggesting heteromerization and mosaic formation between different subtypes and subfamilies of GPCRs as shown for opioid receptor subtypes [28] [29]. The boost in the characterization of 3D crystal structures since publication of the ß 2 -adrenergic receptor structure by Kobilka's group in 2007 [30] gave rise to new challenges to SPECT and PET methods and tracer development as valuable proofs of mathematical models of receptor-ligand interactions in vivo.…”
Section: G Protein-coupled Receptors (Gpcrs)-old and New Approaches Tmentioning
confidence: 99%
“…an α 2A adrenergic-MOR heteromer [28] [29] [35]- [37] guiding future research also to bivalent ligands which could give additional functional informations but also new therapeutic approaches.…”
Section: G Protein-coupled Receptors (Gpcrs)-old and New Approaches Tmentioning
confidence: 99%
“…As certain receptor subtypes, such as dopamine, serotonin, glutamate, and adenosine receptors, have been shown to form GPCR heteromers in vitro in tissue culture and in vivo in animal models, a better understanding of their structure, neuroanatomical location, and physiological function may represent a new target for the design of drugs for the treatment of neuropsychiatric disorders such as schizophrenia, depression, suicidal behavior, and drug abuse. 4548 Here, we will review recent findings related to GPCR heteromers and their role in central nervous system (CNS) function.…”
Section: Role Of Gpcr Heterocomplexes In Neuropsychiatric Disordersmentioning
confidence: 99%
“…117119 Together with coimmunoprecipitation and FRET experiments, 46 the reduction of the affinity of dopamine D2 receptor agonists in the presence of cannabinoid CB1 receptor agonists point toward expression of these two receptors as a GPCR heteromer. 45 It has also been suggested that the antagonistic interactions between cannabinoid CB1 and dopamine D2 receptors as a GPCR heteromer may also involve the adenosine A2A receptor. 120122 This is supported by the demonstration that adenosine A2A receptors directly interact with both dopamine D2 56 and cannabinoid CB1 115 receptors.…”
Section: Adenosine and Dopamine Receptorsmentioning
confidence: 99%